Insider Ownership, Free Cash Flow dan Dividend Policy Perusahaan Manufaktur Terdaftar Di BEJ - Yuniningsih, Yuniningsih (Jurnal Riset Ekonomi dan Bisnis, 2008)
Dividend policy is related to a matter of earning allocation, namely how much of the earning are distributed as dividends and how much of the earning are distributed as retained earnings. Earning matters sometimes result in different desires between management and shareholders, thusly the differences will result in conflicts between both of them and the conflicts will lead to agency cost. The research aimed at analyzing effects of insider ownership and free cash flows on dividen policy partial.The applied data were secondary ones obtained from Jakarta Stock Exchange. Analysis technique applied analysis of multiple linear regression.Research results indicated that insider ownership had no effects on dividend policy, where as free cash flow have effects on dividend policy.Keywords: Dividend Policy, Insider Ownership, Free Cash Flow